multidimensional thinking: towards a more complex and human understanding of rationality - cruz rivera, bibiana judith; mora alonso, césar augusto (childhood & philosophy, 2024)
This article proposes an approach to Matthew Lipman’s philosophical-pedagogical thesis about the multiple transactive dimensions of thinking, namely, critical, creative, and caring thinking. Our goal is to highlight the way in which Lipman’s proposal supports a more complex and humanistic type of rationality. We argue that the interaction and reciprocity that occurs between the three dimensions allows for the emergence of a higher order thinking, namely, reasonableness, which is nothing other than a complex form of rationality, capable of recognizing plurality and diversity. Indeed, this is a rationality that aims to overcome the limitations of prevailing thought, with the intention of avoiding unilateralism, instrumentalism, and scientism. Lipman, the pioneer of the Philosophy for Children Program, affirms that the attainment of reasonableness should be the goal of any educational process; hence, he takes on the task of forging a philosophical-pedagogical proposal, which will be the basis for the deployment of higher thinking skills, and that will also be essential for the construction of a high-quality democracy.